Comparative Study of Performance and Emission Characteristics between Spark Ignition Engine and Homogeneous Charge Compression Ignition Engine (HCCI) - Ali, Nahedh Mahmood (Al-Khwarizmi Engineering Journal, 2017)
Many researchers consider Homogeneous Charge Compression Ignition (HCCI) engine mode as a promising alternative to combustion in Spark Ignition and Compression Ignition Engines. The HCCI engine runs on lean mixtures of fuel and air, and the combustion is produced from the fuel autoignition instead of ignited by a spark. This combustion mode was investigated in this paper. A variable compression ratio, spark ignition engine type TD110 was used in the experiments. The tested fuel was Iraqi conventional gasoline (ON=82). The results showed that HCCI engine can run in very lean equivalence ratios. The brake specific fuel consumption was reduced about 28% compared with a spark ignition engine. The experimental tests showed that the emissions concentrations were reduced by 91.27% for NOx, 85.99% for CO, 78.91% for CO2, and 83.56% for unburned hydrocarbons compared to the SI engine. HCCI engine produced little noise with about 26.68% less than SI engine.